PENERAPAN ASAS EQUALITY BEFORE THE LAW DALAM MEMILIH PENASEHAT HUKUM BAGIANGGOTA MILITER YANGTERLIBATKASUS PIDANA DALAMPERADILANMILITER - Abdul Hamid; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
When members of the Indonesian Armed Forces (TNI) commit a crime or have allegedly committed acrime, whether that is a criminal act regulated in the Criminal Code or outside the Criminal Code and acriminal act enshrined in the Criminal Code. The TNI member was based on the provisions of Law Number 39of 1997 concerning Military Courts and could not freely and independently elect his legal counsel who wasbelieved to be able to assist his legal process. The authority to determine legal counsel is determined by thePerkatra Submission Officer (PAPERA). This is very different from non-military citizens when committing acrime, he is free to appoint and determine their own legal counsel. The purpose of writing this thesis, namely;First, to find out the freedom to choose legal counsel for military members involved in criminal cases inmilitary criminal justice is associated with the principle of equality before the law, Second, to find out the legalconsequences for legal counsel who do not get permission from the Conquering Officer (PAPERA).This type of research can be classified as normative legal research. Because this research is morespecific to the principle of equality before the law or equality of citizens before the law. Sources of data usedare primary data legal materials, secondary data and tertiary data. For the technique of collecting researchdata, the authors conducted a literature study.From the results of the research based on the formulation of the problem, it is known that the applicationof the principle of equality before the law in selecting legal advisors for military members committing a crimeor to be suspected of having committed a crime is not appropriate as the principle should be. The TNI's internalunit has indeed provided legal aid services based on the determination from PAPERA. But for military memberswho want to use legal aid services from outside the TNI must be based on permission from PAPERA. If they donot get permission from PAPERA, the legal advisor / advocate cannot go to court to help the legal process ofhis client. Meanwhile, there is no legal provision for PAPERA to determine whether or not the advocate iseligible for permission. Even if a TNI member commits a criminal offense, based on the constitution of a TNImember it is still a citizen who must get the same treatment before the law. So it is necessary to do a legalrenewal of Law Number 39 of 1997 concerning Military Justice. Especially related to the freedom of a militarymember to determine his legal counsel.Keywords: Equality before the law, Legal advisor, Papera